PENGARUH PENGUNAAN MEDIA CHEMCROSSWORD PUZZLE TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA SMP NEGERI 16 PONTIANAK - Berliana, Netty; Enawati, Eny; Lestari, Ira (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis aim of this research was to know the influence of chemcrossword puzzle on student motivation and study result. Method of this research is quasi experimental design with nonequivalent control grup design. Populations of this research are VIII grade student of Smp N 16 Pontianak academic year 2014/2015. This research used purposive sampling technique to select the experiment class and control class. Tool of data collecting is motivation questionnaire and tes. Based on data analysis, it has been found that there is a difference in control class motivation of 58.86% with sufficient categories and experimental class of 78.30% with strong categories. Analysis of posttest data using the U-Mann Whitney test obtained in the sig (2-tailed) 0f 0.003 asymp, this indicates that there are differences in experimental class student learning outcomes with the control class. chemcrossword give influenced by 27,34% towards the increasing in students learning outcomes in zat adiktif dan psikotropika solutions material at SMP N16 Pontianak. Â keywords: chemcrossword puzzle